Layanan Konseling Berbasis Komunitas Bagi Klien di Balai Rehabilitasi Sosial - Nur Azizah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2019)
The beneficiaries or Persons with Social Welfare Problems (PMKS) at the Social Rehabilitation Center cannot be separated from problems that arise both from before and during their stay or undergoing rehabilitation. Therefore counseling is expected to be one of the services that can be provided to help beneficiaries with various problems. their respective characteristics. This study uses a qualitative approach with a descriptive type of research to find out the Counseling Service Model at Beneficiaries at the Social Rehabilitation Center (Ex-Residency District of Banyumas). This research was conducted at the "Satria" Drug Abuse Victims Social Institution (PSRSKP) in Baturaden, where beneficiaries were called residents of drug users and at the "Sudagaran" Banyumas Elderly Social Service Home (PPSLU), where beneficiaries consisted of foster children and elderly (elderly). The results of his research showed that the Counseling Service Model for Beneficiaries at the Social Abuse Rehabilitation Social Institution (PSRSKP) Drug "Satria" in Baturaden was conducted when the resident would begin rehabilitation and counseling activities both individual counseling or integrated group counseling in Therapeutic Community activities (TC ) also called Community Therapy facilitated by social workers assisted by counselors. While the Counseling Service Model for Beneficiaries at the "Sudagaran" Banyumas Elderly Social Service Institution (PPSLU), conducted based on problems found and arising in beneficiaries carried out through individual counseling or group counseling facilitated by social workers and employees.Keywords: Model, Counseling, Beneficiaries.